Containers and Packaging Fruits & Vegetables - Gast, Karen L. B. (My University, 1991)
Publication describes proper packaging for a grower selling to a wholesale fruit and vegetable buyer, and industry standards.
MF979_1991_03
Keywords: MF979; Equipment and Structures; Fruits and Vegetables; MF